1999
DOI: 10.1021/bi990456x
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structure of an Antisense DNA·RNA Hybrid Duplex Containing a 3‘-CH2N(CH3)-O-5‘ or an MMI Backbone Linker

Abstract: The solution structure of an antisense DNA.RNA hybrid duplex, d(CGCGTT-MMI-TTGCGC).r(GCGCAAAACGCG) (designated R4), containing an MMI backbone linker [3'-CH(2)N(CH(3))-O5'], is elucidated. The structural details of the MMI linker, its structural effects on the neighboring residues, and the molecular basis of the MMI effects are examined. The lipophilic N-methyl group of MMI is peripheral to the helix, assuming a conformation that is most stable with regard to the N-O torsion angle. The MMI linker promotes a 3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Thus far, oligonucleotide N3′ → P5′phosphoramidates ( 29 ) and ONs containing 3′-methylene backbones (3′-methylene phosphonate backbone, methylene methylimino backbone and amide backbone) ( 30 32 ) composed of 2′-deoxyfuranose-based nucleosides are known RNA-like molecules. The nucleoside units of those modified ONs prefer the 3′-endo sugar conformation in solution ( 31 , 33 ), while that of 4′-thioDNA adopts a 2′-endo sugar conformation in solution and crystals ( 34 ). It is nevertheless worth noting that, despite such structural differences in nucleoside units, 4′-thioDNA can adopt an RNA-like conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, oligonucleotide N3′ → P5′phosphoramidates ( 29 ) and ONs containing 3′-methylene backbones (3′-methylene phosphonate backbone, methylene methylimino backbone and amide backbone) ( 30 32 ) composed of 2′-deoxyfuranose-based nucleosides are known RNA-like molecules. The nucleoside units of those modified ONs prefer the 3′-endo sugar conformation in solution ( 31 , 33 ), while that of 4′-thioDNA adopts a 2′-endo sugar conformation in solution and crystals ( 34 ). It is nevertheless worth noting that, despite such structural differences in nucleoside units, 4′-thioDNA can adopt an RNA-like conformation.…”
Section: Discussionmentioning
confidence: 99%
“…The PO linkage can also be replaced with other nitrogen containing achiral four atom linkages. 74 Sanghvi et al showed that the methylene-(methylimino) (MMI) linkage can be an effective replacement for the PO linkage (Figure 6). 75 Like the amide linkage, the thermal stability of MMI linked dimers can be further enhanced by incorporating a fluorine atom or a methoxy group at the 2′position (ΔT m 3.2 to 3.7 °C per dimer modification).…”
Section: Methylene(methylimino) (Mmi)mentioning
confidence: 99%
“…The PO linkage can also be replaced with other nitrogen containing achiral four atom linkages . Sanghvi et al showed that the methylene­(methylimino) (MMI) linkage can be an effective replacement for the PO linkage (Figure ).…”
Section: Backbone Modificationsmentioning
confidence: 99%
“…Planarity constraints were applied to all except the terminal base‐pairs 49. Backbone torsion angles were loosely constrained to a range which encompassed typical values for both A‐ and B‐type helices, in accordance with the literature 49,50. For the modified triplex, torsion angles were not additionally constrained for the Hoogsteen bonded strand 51.…”
Section: Methodsmentioning
confidence: 99%